Study the Level of Collagen2-1NO2 (Coll2-1NO2) in Serum of Iraqi Patients with Osteoarthritis - Huda S. Mutar, Bushra F. Hasan, Samer Abdulhasan Muhi (Pakistan Journal of Medical & Health Sciences, 2022)
Osteoarthritis, often known as OA, is characterized by the degeneration of articular cartilage, limited intraarticular inflammation with synovitis, and peri-articular and subchondral bone changes. This study measured Coll2-1NO2, CRP, ESR, Vitamin D3, Mg, Calcium, and Lipid profiles in OA patients. The current study contained a total of 130 participants, who were divided into two groups. Group1 contained 90 OA patients, and group 2 controls 40; the samples were extracted from females and males, the levels, Coll2-1 NO2, CRP, ESR , Vitamin D3 ,Mg, Calcium, Cholesterol, TG, VLDL, LDL, and HDL were calculated. The levels of Coll2-1NO2, CRP, and Vitamin D3 were evaluated using an enzyme-linked immunosorbent assay (ELISA), while the levels of Mg, Calcium, Cholesterol, TG, VLDL, LDL, and HDL were determined using a Human Reader HS Device. Westergren method was used to analyze the level of ESR . The result of Coll2-1NO2 shows a high significant change among OA patients and control. Serum vitamin D3 and CRP value have high significant change in their levels in OA patients. Serum levels of Triglyceride, HDL, Mg, Ca, ESR and VLDL showed a significant variation among OA patient and control. Cholesterol and LDL values have non-significant variation in their levels in OA patients in comparison with control. Conclusion: According to the presented results Coll2-1NO2, CRP, ESR, Vitamin D3, Mg, Calcium, T.G, VLDL, and HDL do affect by Osteoarthritis patients. LDL and cholesterol don’t affect osteoarthritis patients